2013
DOI: 10.3402/gha.v6i0.20066
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the influence of television advertisements on children and caries prevalence

Abstract: IntroductionChildren watch television during most of their free time. They are exposed to advertisers’ messages and are vulnerable to sophisticated advertisements of foods often detrimental to oral and general health.ObjectivesTo evaluate the influence of television advertisements on children, the relationship with oral health and to analyze the content of those advertisements.MethodologyA questionnaire-based study was performed among 600 schoolchildren of Mangalore, Karnataka, followed by oral examination. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
1
29
0
3
Order By: Relevance
“…The study demonstrated a strong association between the daily time spent by schoolchildren watching TV and outcomes. Schoolchildren who indicated that they watched TV for more than 90 min were more likely to consume cariogenic foods and have a higher rates of caries, which corroborates the findings of other studies showing that greater time spent watching TV is associated with the risk of developing dental caries(Ghimire & Rao, ; Zeng, Sheiham, & Sabbah, ). Moreover, most participants reported buying or asking their parents to buy products viewed in TV advertisements, with most products referring to food.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated a strong association between the daily time spent by schoolchildren watching TV and outcomes. Schoolchildren who indicated that they watched TV for more than 90 min were more likely to consume cariogenic foods and have a higher rates of caries, which corroborates the findings of other studies showing that greater time spent watching TV is associated with the risk of developing dental caries(Ghimire & Rao, ; Zeng, Sheiham, & Sabbah, ). Moreover, most participants reported buying or asking their parents to buy products viewed in TV advertisements, with most products referring to food.…”
Section: Discussionmentioning
confidence: 99%
“…observed that children who watched more TV had worse oral hygiene and consumed larger amounts of soft drinks compared with children who watched less TV. Ghimire and Rao found that children who like to watch TV advertisements, and especially those who pester their parents to buy them the foods advertised, have a higher DMFT index.…”
Section: Discussionmentioning
confidence: 99%
“…The commercialization of children's television programs, banners, and posters are the several concerns raised by child health professionals, regarding the impact of advertisements on children's wellbeing [6]. The current study was done to evaluate the influence of television advertisements, comics/magazines and banners/ posters on children and the impact on oral health.…”
Section: Discussionmentioning
confidence: 99%